Home Quarantine Among COVID Positive Health Professionals: A Cross-Sectional Study From Hyderabad Pakistan - Parveen, Naheed; Abbasi, Madiha; Siddiqui, Erum; Awan, Shazia; Akhtar, Muhammad Naveed; Sikandar, Raheel (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the preference for home quarantine and its reasons among health professionals during the COVID-19 pandemic. Study Design: Cross-sectional study. Place and Duration: Department of Obstetrics/Gynecology, Liaquat University of Medical and Health Sciences Jamshoro, and other affiliated hospitals with LUMHS, from Apr to Sep 2021. Methodology: Eighty home-quarantined health professionals (HPs) at our institute following the exposure to confirm COVID-19 cases were included. A pre-designed questionnaire was used to analyze its reliability using Cronbach’s alpha value in SPSS after completing the home quarantine period and analyzed. Results: We enrolled 80 health professionals. 43 (53.8%) were PG Trainees, followed by consultant (20%), doctors (20.0%), nurses (6.2%), and technicians (6.9%). The mean quarantined period was 15.72 ± 6.15 days (7-20 days). Doctors, PG trainees, and nurses perceived a greater level of irritability than the other health professionals. We found an association between irritability and advanced age, confinement, and being single. Generally, PG Trainee revealed higher physical activity (p= <0.001). Physical activity was significantly lower among respondents who were unmarried (p= 0.004). Conclusion: Increased satisfaction and a more homelike environment, less aggravation of symptoms, and a mild level of depression and anxiety among health care professionals were associated with home quarantine measures during the COVID19 pandemic.